Umbanda: Hybridity, Tradition and Semantic Plurality - Engler, Steven (Interdisciplinary Journal for Religion and Transformation in Contemporary Society, 2022)
Abstract Focusing on the Brazilian spirit-incorporation religion of Umbanda, this article proposes a theoretical shift in conceptions of hybridity: a move from asking "what ingredients mix in what manner to produce what result?"to asking "how do we interpret religious innovation?"This approach sees meaning as simply the result of interpretation (not in terms of a representational relation between words and world). It also underlines the centrality of discursive claims of hybridity and purity, as opposed to historical issues of origins - a point clarified by comparing "hybridity"to "tradition."Comparison of Umbanda and Candomblé leads to the conclusion that each can be considered both "Afro-Brazilian"and "hybrid"in different ways. Candomblé exhibits semantic polarity (all groups accept that a certain sub-type is more authentic and hybridity marks divergence from that norm). Umbanda exhibits semantic plurality (wide variation between groups is not subject to such a normative judgment). Keywords
Created from Fastlane, Scopus look-up
Keywords: Afro-brazilian religions; Candomblé; Hybridity; Semantics; Tradition; Umbanda